2023
DOI: 10.29228/jrp.348
|View full text |Cite
|
Sign up to set email alerts
|

Identification of major phenolic compounds of Aloe vera and its protective effect on ovaries under oxidative stress in diabetic rats

Abstract: The study investigated the major phenolic compounds of Aloe vera leaf (AVL) by the high-performance liquid chromatography (HPLC) method, and its protective effect on ovaries under oxidative stress of streptozotocininduced diabetic rats. The study was conducted on control (untreated healthy rats; C), diabetes (untreated diabetic rats; D) and diabetes+A. vera treatment (diabetic rats treated with A. vera; D+A) groups. D+A group was given an ethanolic extract of A. vera (300 mg/kg) for 14 days. Major phenolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Diabetes mellitus, which is an important health problem for humans, has been studied many times, and it is still one of the most frequently studied subjects in the scientific world [19,20,24]. In many of these studies, histopathologic examination was performed, and it was revealed that diabetes has a splenotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes mellitus, which is an important health problem for humans, has been studied many times, and it is still one of the most frequently studied subjects in the scientific world [19,20,24]. In many of these studies, histopathologic examination was performed, and it was revealed that diabetes has a splenotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Animals in Diabetes + Treatment 1, Diabetes + Treatment 2, and Diabetes + Treatment 3 groups were administered 50 mg/kg, 100 mg/kg, and 200 mg/kg of Gundelia tournefortii extract daily by oral gavage for 21 days, respectively. At the end of the experiment, animals were sacrificed under general anesthesia (Xylazine 10 mg/kg and Ketamine 5 mg/kg), and spleen tissues were removed under appropriate storage conditions [19].…”
Section: Animal Groups and Treatment Schedulementioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds show strong antioxidant effects in general. [1][2][3][4] Rutin is also called vitamin P in some sources and stands out by exhibiting a variety of pharmacological actions, including anti-inammatory, anti-allergic, antioxidant, antidiabetic, antihypertensive, cardioprotective, and neuroprotective effects. 5,6 RUT is included in many plants that people frequently consume daily, such as coffee, rooibos, buckwheat, etc.…”
Section: Introductionmentioning
confidence: 99%